1982
DOI: 10.1055/s-2007-1019111
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Alanine by Hypothyroid and Growth Hormone Treated Hypothyroid Rats, their Fetuses and Progeny

Abstract: Maternal thyroidectomy (Tx) results in decreased maternal and fetal liver glycogen and protein as well as fetal serum glucose and maternal and fetal serum protein on the 22nd day of gestation. Progeny of Tx mothers continue to show reduced serum and liver protein levels at 1, 5 and 30 days of age. Their serum glucose is also depressed at 1 and 5 days of age but is elevated over that of control progeny by 30 days of age; whereas, liver glycogen is elevated at 1 day of age but is similar to control progeny at 5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

1984
1984
1993
1993

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…We have demonstrated in previous studies that amino acid uptake and utilization in brain and brain protein and glycoprotein synthesis are impaired in the fetuses, neonates, and adult progenies of Tx mothers [16,17,20]. In fact, in some recent studies we find the extracellular to intracellular ratios of most free amino acids to be exceptionally low in the offspring of Tx mothers [unpublished observations].…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…We have demonstrated in previous studies that amino acid uptake and utilization in brain and brain protein and glycoprotein synthesis are impaired in the fetuses, neonates, and adult progenies of Tx mothers [16,17,20]. In fact, in some recent studies we find the extracellular to intracellular ratios of most free amino acids to be exceptionally low in the offspring of Tx mothers [unpublished observations].…”
Section: Discussionmentioning
confidence: 96%
“…This concept is in accord with that of G ina I ska -Matin o wska and Romer [15] who suggest that GH exerts its effects by altering or promoting placental develop ment. Our previous studies have, indeed, shown that many of the fetal and neonatal metabolic aberrations produced by maternal Tx are corrected by GH treatment oftheTx mother [16,17,20,32,34,35], especially amino acid supply to and protein synthesis in brain of fetuses and neonates [16,17,20]. The fact that GH treatment of the Tx mother normalizes protein-RNA synthesis and that memory is significantly improved also in the progenies of these mothers may point to one of the most important aspects of these studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They have deficient cellular amino acid uptake and protein synthesis in brain, liver and skeletal muscle (Hendrich, Wiedmeier and Porterfield 1982;Hendrich and Porterfield 1980). At the time of birth, these pups have fewer brain and liver cells and much lower protein concentrations in these tissues (Porterfield and Hendrich 1982). Furthermore, total brain and liver RNA are low in the perinate (Porterfield and Hendrich 1982).…”
Section: Introductionmentioning
confidence: 98%